Case Report: A Novel NKX2-5 Mutation in a Family With Congenital Heart Defects, Left Ventricular Non-compaction, Conduction Disease, and Sudden Cardiac Death - Morlanes-Gracia, Paula; Antoniutti, Guido; Alvarez-Rubio, Jorge; Torres-Juan, Laura; Heine-Suñer, Damian; Ripoll-Vera, Tomás (Frontiers in Cardiovascular Medicine, 2021)
The NKX2-5 gene encodes for a transcription factor crucial for cardiac cell differentiation and proliferation. It was the first gene associated with congenital heart disease (CHD) in humans and has been linked to conduction disorders or cardiomyopathies. However, an overlapping phenotype is not frequent in the literature. We describe a family with a novel missense mutation in the NKX2-5 gene (p.Gln181Pro) with numerous antecedents with atrial septal defect (ASD), left ventricular non-compaction (LVNC), conduction disease and sudden cardiac death (SCD).